A method for estimation of complex permittivities of 3-D inhomogeneous biological bodies (software development) / Jafni Baharudin - Baharudin, Jafni (1996)
Complex permittivities are estimated for a 36-cefis model which represent me chest portion of the block model of man by using moment method formulation of the electric field integral equation.. The saline/ water can beused asa sunoundmg medium to get a lower error in calculated complex permittivities as compared to the air, on account of batter matching of energy to me biologtcal body. The mverse proMem can solved for a small number of buried cells but become illposed and unsolved for large number of buried cells